Вплив хімічного складу титанових сплавів на межу міцності холоднокатаних труб - Міщенко, О.В. (Physico-technological Institute of Metals and Alloys, 2023)
Industrial studies of the chemical composition and mechanical properties of pipes made of 186 melts of the VT1-0 alloy were carried out. It is determined that the content of impurities in modern alloys is significantly lower than the limits specified in the standards. The influence of the main elements of the chemical composition of the alloy on the ultimate strength of cold-rolled pipes is analyzed. Graphs of the dependences of the strength limit values on the content of the main chemical elements are constructed. The range of dispersion of values of the ultimate strength of pipes made of VT1-0 alloy for all 186 melts is established. Based on the obtained data, a diagram of the frequency distribution of tensile strength is constructed and average values, the standard deviation and the coefficient of variation for the batch of pipes are determined. The pattern of distribution of the strength limit of the studied pipes corresponds to the normal Gauss distribution. The average strength of the pipes is 505 H/mm2, the average square deviation is 14 H/mm2, and the coefficient of variation is 2.8 %. It is noted that in the production of pipes of the same size according to the same technological standards of production, pipes from the different melting number have a wide range of tensile strength. It is shown that when considering the content of carbon, iron, oxygen, aluminium and hydrogen in the considered ranges for the VT1-0 alloy, it practically does not affect the strength limit of coldrolled pipes. The results of research in terms of estimating the range of variation in the values of the ultimate strength of pipes in industrial batches of VT1-0 alloy can be extended to pipes from other titanium-based alloys. It is recommended to change the requirements for regulating the ranges of chemical elements in titanium alloys, VT1-0 and similar, during their melting. The obtained data allow us to refine the calculations of energy-power parameters of the cold rolling process of pipes made of titanium alloys and technological modes of production.